The Effect of Progressive Muscle Relaxation (PMR) Therapy on Reducing Blood Pressure in Hypertensive Elderly in The Working Area of the Andalas Public Health Center - Lailatul Syahadah Zailani; Defi Yulita; Ledia Restipa (STIKes Alifah Padang, 2023)
There is an increase of 63,309,620 people had hypertension in Indonesia in the year of 2018. In Padang City it was 21.75%. The highest hypertension occurred in the 54-64 year age group (55.2%). One way to reduce hypertension is non-pharmacological (Progressive Muscle Relaxation therapy). The aim of this study was to determine the effect of Progressive Muscle Relaxation (PMR) therapy on reducing blood pressure in hypertensive elderly in the Andalas Public Health Center Work Area. This type of research is a pre-experiment method, with a One Group pre-test post-test design. The research was conducted on 3-30 May 2023. The population in this study was 968 hypertensive elderly, a sample of 28 people with a sampling technique using purposive sampling. Data was collected using an observation sheet. Data were analyzed univariately and bivariately using the Wilcoxon statistical test. Based on the research results, it was found that before therapy, the systolic blood pressure was 152.54 mmHg with SD 8.639 and diastolic 86.50 with SD 5.514, while after therapy the systolic blood pressure was 149.50 mmHg with SD 8.284 and diastolic 84 mmHg with SD 4.073. The difference between systolic blood pressure is 3.04 mmHg and diastolic 2.50 mmHg. There is an effect of progressive muscle relaxation (PMR) therapy on reducing blood pressure in hypertensive elderly with P-Value = 0.000 (< 0.05). Based on the research results, it can be concluded that there is an influence of Progressive Muscle Relaxation (PMR) therapy on reducing blood pressure in hypertensive elderly in the Andalas Health Center Working Area.